Layer-structured LiNi0.8Co0.2O2: A new triple (H+ /O2− /e−) conducting cathode for low temperature proton conducting solid oxide fuel cells - Fan, Liangdong (2017)
Solid oxide fuel cells with proton conducting electrolytes (H–SOFCs) show great potential for more efficient energy conversion over their oxygen ionic conducting counterparts at temperatures below 650 °C, providing a comparably high performance cathode material can be available. A brief review of current development of cathode materials shows that materials with triple (oxygen ionic, protonic, and electronic) conducting properties are most promising for H–SOFCs. In this work, a triple-conducting LiNi0.8Co0.2O2 (LNCO) with layered structure, allowing simultaneous conduction of intrinsic oxygen ion and electron as well as the extrinsic proton, is proposed as a cathode material for H–SOFC. The electrochemical impedance spectroscopy analysis of LNCO shows the good oxygen reduction reaction (ORR) activity with a considerably low activation energy of 0.88 eV, and an evident water uptake capability those facilitate the cathode reaction process. Fuel cells using LNCO cathode on a BaZr0.1Ce0.7Y0.2O3 proton-conducting electrolyte render a peak power density of 410 mW cm−2 at 650 °C under H2/air condition, which is higher than most of the typical cathode materials reported with similar cell configurations. This work also demonstrated a new series of simple and low cost cathode materials simultaneously possessing interesting triple-conduction and good ORR activities for low temperature H–SOFCs.